Social implications arise in embodied music cognition research which can counter musicological “individualism” - Moran, Nikki (Frontiers in Psychology, 2014)
The agenda in music research that is broadly recognized as embodied music cognition has arrived hand-in-hand with a social interpretation of music, focusing on the real-world basis of its performance, and fostering an empirical approach to musician movement regarding the communicative function and potential of those movements. However, embodied cognition emerged from traditional cognitivism, which produced a body of scientific explanation of music-theoretic concepts. The analytical object of this corpus is based on the particular imagined encounter of a listener responding to an idealised ‘work’. Although this problem of essentialism has been identified within mainstream musicology, the lingering effects may spill over into interdisciplinary, empirical research. This paper defines the situation according to its legacy of individualism, and offers an alternative sketch of musical activity as performance event, a model that highlights the social interaction processes at the heart of musical behaviour. I describe some recent empirical work based on interaction-oriented approaches, arguing that this particular focus – on the social interaction process itself – creates a distinctive and promising agenda for further research into embodied music cognition.